Rise : From Caged Bird to Poet of the People, Maya Angelou - Hegedus, Bethany; Johnson, Colin A. (Colin Ashanti); Engel, Tonya (New York : Lee & Low Books Inc., 2019)
"A biography of African American writer, performer, and activist Maya Angelou, who turned a childhood of trauma and emotional pain to become one of the most inspiring voices of our lifetime. Includes afterword, author's note, and sources"--
Includes bibliographical references.
Keywords: Angelou, Maya -- Juvenile literature; Angelou, Maya; African American women authors -- Biography -- 20th century; African American women authors -- Biography -- 20th century; Biographies